PERBANDINGAN WAKTU EKSEKUSI PERAMALAN HARGA KOMODITAS PANGAN MENGGUNAKAN SPARKR DAN R STUDIO - Dedy Sugiarto; Dimmas Mulya; Abdul Rochman; Is Mardianto (Universitas Palangka Raya, 2022)
The arrival of the big data era with characteristics such as large volumes of data makes the calculation of execution time a concern when carrying out data analytics processes, such as forecasting food commodity prices. This study aims to examine the effect of the big data framework through the use of sparkR. The test is carried out by varying several deep learning forecasting models, namely the multi-layer perceptron model and by using the price of one food commodity from 2018 to 2020. The results show that sparkR is significantly shorter its execution time when compared to R studio. The results of testing the influence of the MLP model also show that a model with two hidden layers with a maximum node of 13 nodes in hidden layers 1 and 2 produces the longest execution time compared to only using 1 hidden layer with 5 nodes or using two hidden layers with a number of nodes of 5 and 3.